2008
DOI: 10.1055/s-2008-1053519
|View full text |Cite
|
Sign up to set email alerts
|

Zerebrale Dysfunktion bei Patienten mit idiopathischer Skoliose

Abstract: To determine a possible involvement of CNS in the etiology of the socalled idiopathic scoliosis, some 115 clinically neurologically and psychically inconspicuous patients suffering from idiopathic scoliosis and some 35 patients with congential scoliosis have been submitted to EEG control. The idiopathic scoliosis group showed a significant percentage of divergence from normal EEG results found in the average normal population. The type and the genesis of the cerebral dysfunction as well as a possible correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Robb et al reported that patients with AIS showed a difference in brain responsiveness, showing similar electroencephalography (EEG) results to the control group [11]. At the same time, pathological abnormality in subcortical structures may be present due to increased low-frequency brain activity and proximal activity in patients with AIS [12,13]. Pathological EEG results were found in the contralateral hemisphere in AIS patients with lumbar curvature, the ipsilateral hemisphere in patients with thoracolumbar curvature, and the bilateral hemisphere in patients with thoracic curvature [13].…”
Section: Introductionmentioning
confidence: 92%
“…Robb et al reported that patients with AIS showed a difference in brain responsiveness, showing similar electroencephalography (EEG) results to the control group [11]. At the same time, pathological abnormality in subcortical structures may be present due to increased low-frequency brain activity and proximal activity in patients with AIS [12,13]. Pathological EEG results were found in the contralateral hemisphere in AIS patients with lumbar curvature, the ipsilateral hemisphere in patients with thoracolumbar curvature, and the bilateral hemisphere in patients with thoracic curvature [13].…”
Section: Introductionmentioning
confidence: 92%
“…In this context, Robb et al indicated that there was no difference in EEG results similar between AIS and CG (8). In contrast, It was suggested that pathological changes may have occurred in subcortical structures due to increased low-frequency brain activities and observation of paroxysmal activity in AIS and that cerebellar dysfunction may be related to its etiology (9,10). Besides differences in brain responses, hemispheric changes associated with the type of curvature has drawn attention.…”
Section: Introductionmentioning
confidence: 99%
“…However, there was a significant difference in brain responses between patients with AIS and CG in this study like other studies (15). Lukeschitsch et al, Deratakis et al, and Sahlstrand et al reported that the idiopathic scoliosis group differed significantly from EEG results in a healthy population(9,10,16).…”
mentioning
confidence: 97%